Individual and Collective Actions Against Climate Change Among Chinese Adults: The Effects of Risk, Efficacy, and Consideration of Future Consequences. Issue 2 (April 2023) - Shi, Jingyuan; Li, Zixi; Chen, Liang; Tang, Hongjie
In this study, we tested the core premise of the risk perception attitude framework—that perceived risk and perceived efficacy jointly affect intention—and identified consideration of future consequences (CFC) as a boundary condition of the premise in the context of mitigating climate change. Our two-wave survey ( N = 439) revealed that perceived individual-level efficacy predicted intention to perform individual behavior, whereas perceived societal-level risk predicted intention to engage in collective action. For individuals with low CFC, perceived risk and perceived efficacy's joint effect was positively associated with intention to engage in individual behavior and collective action against climate change.